BASIC RULES FOR ACCOUNTING FOR TANGIBLE AND INTANGIBLE ASSETS IN NATIONAL ACCOUNTING STANDARDS - Rakhmanova , Shakhnoza (Effective scientific journals, 2025)
This article analyzes the main rules for recognition, measurement, depreciation and presentation of tangible and intangible assets in financial statements in accordance with the National Accounting Standards of the Republic of Uzbekistan. Particular attention is paid to NAS No.5 “Intangible Assets” and NAS No.6 “Property, Plant and Equipment”, as well as their comparison with International Financial Reporting Standards IAS 38 and IAS 16. Based on the analysis of Uzbek and international practices, existing problems in accounting for intangible assets are identified, and practical recommendations are proposed to improve accounting practices in the context of global financial integration.